Perception of human rights violations against people on the move - Σβολιαντοπούλου, Σοφία (Πανεπιστήμιο Πελοποννήσου, 2018)
Immigration it is not an issue of today. People were moving since the very early times of their existence. The only thing that have changed is the reasons. They used to move to other places because of the weather, the needs of the animals, to find better place for agriculture, but also because of their curiosity. Today, two are the many reasons for a person leaving its home: fear of his life and the hope for a better chance. The last years the flows of immigrants in Europe and especially in Greece, Italy and Turkey are enormous. Those people are not only suffering the loss of their previous lives, but they have to face also the loss and violation of their basic human Rights. Human Rights, were firstly mentioned in the Geneva Convention and in the Universal Declaration of Human Rights. Article 1 says: “All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood”. Main points of the declaration is also the freedom of movement, the right to food and health and the freedom of speech and political expressions. The refugees are leaving their countries facing serious violation of human rights such as threat to life and they are coming here, in Europe, to face even worse. In this paper, after referring to all the conventions that secure human rights, we will find out through examples and person stories how those rights of the people on the move are violated in Greece, what can the Greek government and EU can to do to ameliorate the situation and which are the rights that have been violated repeatedly, and made those vulnerable people to even think going back to their countries. In this point I want to thank all the refugees, volunteers and researchers that helped me doing this case study. Your voice can be heard, even if your names will not.
Keywords: Προσφυγική κρίση; Πρόσφυγες; Μεταναστευτική πολιτική; Μετανάστευση; Πρόσφυγες; Ανθρώπινα δικαιώματα; Διεθνές ανθρωπιστικό δίκαιο; Ρατσισμός